Life cycle assessment of Jatropha biodiesel as transportation fuel in rural India - Achten, W.M.J.; Almeida, J.; Fobelets, V.; Bolle, E.; Mathijs, E.; Singh, Virendra Pal; Tewari, D.N.; Verchot, Louis V.; Muys, B. (2010)
Since 2003 India has been actively promoting the cultivation of Jatropha on unproductive and degraded lands (wastelands) for the production of biodiesel suitable as transportation fuel. In this paper the life cycle energy balance, global warming potential, acidification potential, eutrophication potential and land use impact on ecosystem quality is evaluated for a small scale, low-input Jatropha biodiesel system established on wasteland in rural India. In addition to the life cycle assessment of the case at hand, the environmental performance of the same system expanded with a biogas installation digesting seed cake was quantified. The environmental impacts were compared to the life cycle impacts of a fossil fuel reference system delivering the same amount of products and functions as the Jatropha biodiesel system under research. The results show that the production and use of Jatropha biodiesel triggers an 82% decrease in non-renewable energy requirement (Net Energy Ratio, NER = 1.85) and a 55% reduction in global warming potential (GWP) compared to the reference fossil-fuel based system. However, there is an increase in acidification (49%) and eutrophication (430%) from the Jatropha system relative to the reference case. Although adding biogas production to the system boosts the energy efficiency of the system (NER = 3.40), the GWP reduction would not increase (51%) due to additional CH4 emissions. For the land use impact, Jatropha improved the structural ecosystem quality when planted on wasteland, but reduced the functional ecosystem quality. Fertilizer application (mainly N) is an important contributor to most negative impact categories. Optimizing fertilization, agronomic practices and genetics are the major system improvement options.